Circulating microparticles remain associated with complement activation despite intensive anti-inflammatory therapy in early rheumatoid arthritis. Issue 7 (16th November 2009) - van Eijk, I C; Tushuizen, M E; Sturk, A; Dijkmans, B A C; Boers, M; Voskuyl, A E; Diamant, M; Wolbink, G J; Nieuwland, R; Nurmohamed, M T
Abstract : Objectives: Rheumatoid arthritis (RA) is a chronic systemic inflammatory disease characterised by synovitis and joint destruction. The pathogenesis of RA is not clear, but is considered to be an immune-mediated inflammatory disorder, in which the complement system plays an important role. Although cell-derived microparticles (MPs) have been associated with inflammation and complement activation, it is unknown whether MPs are either cause or consequence. Therefore, we investigated whether circulating MPs differ between patients with very early as yet untreated arthritis and healthy controls, and whether intensive anti-inflammatory treatment of such patients affects circulating MPs. Methods: Patients with RA (n=24) and controls (n=15) were included. Nine patients with RA were re-evaluated after 8 weeks of intensive treatment with a combination of drugs ('COmBination therapy in Rheumatoid Arthritis' (COBRA) scheme). Disease activity was measured by erythrocyte sedimentation rate (ESR), C reactive protein (CRP) and Disease Activity Score for 28 joints (DAS28). Flow cytometry was used to study MPs and exposure of complement activator molecules and complement components. Results: At baseline, concentrations of MPs exposing C1q, CRP or serum amyloid-P (SAP)were all significantly elevated in patients with early RA compared to controls (p=0.003, p=0.002 and p=0.003, respectively). Upon treatment, DAS28 score, ESR and CRP levels significantly decreased (p=0.008, p=0.008 and p=0.012), but the concentrations of circulating MPs and MPs exposing complement components or activator molecules were unaffected. Conclusion: Circulating MPs exposing complement components or activator molecules are elevated in early RA. Since a strong anti-inflammatory therapy suppressed inflammation in patients with early RA but not levels of circulating MPs, it is unlikely that inflammation is the main underlying cause of MP release in these patients.